'Oh, what a tangled web we weave': How tax linkages shape responsiveness in the United Kingdom and France. (May 2020) - Truchlewski, Zbigniew
What determines government responsiveness during fiscal austerity? Comparing the United Kingdom (UK) and France between 1975 and 2015 and using narrative accounts of austerity episodes, I argue that tax linkages (defined as the nature of dominant taxes, their governance and their dilemmas) shape partisan competition and fiscal responsiveness. I show how, despite comparable conditions, the UK and France implemented austerity simultaneously but opted for divergent types of fiscal responsiveness. In the UK, the right has been advantaged by centralized and weak tax linkages, which acted as a break on tax hikes and favoured spending cuts. In France, the left benefited from decentralized and strong tax linkages, which helped to increase taxes and made it hard to cut spending.